From bench to bedside a comprehensive review of pancreatic cancer immunotherapy. Issue 1 (December 2016) - Kunk, Paul; Bauer, Todd; Slingluff, Craig; Rahma, Osama
Abstract The incidence of pancreatic cancer has been increasing while its 5-year survival rate has not changed in decades. In the era of personalized medicine, immunotherapy has emerged as a promising treatment modality in a variety of malignancies, including pancreatic cancer. This review will discuss the unique pancreatic tumor microenvironment, including the cells and receptors that transform the pancreas from its normal architecture into a complex mix of suppressor immune cells and dense extracellular matrix that allows for the unrestricted growth of cancer cells. Next, we will highlight the recently completed immunotherapy clinical trials in pancreatic cancer. Finally, we will explore the on-going immunotherapy clinical trials and future directions of this engaging and changing field.